How to Differentiate Instruction for Deeper Learning Using Cognitive Task Analysis - Juwita, Ratna; Sukmawati, Fatma; Santosa, Eka Budhi; Cahyono, Budi Tri; Prihatin, Relly; Suparmi, Suparmi; Ridhani, Jovita; Trisnaningsih, Sari (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2025)
This study aims to explore the requisite skills for Differentiated instruction (DI) implementation and to identify best practices across school levels. Differentiated instruction (DI) for deeper learning is essential for responding to students’ diverse needs. Using 112 self-reported essays, interviews, videotaped practices, and experts meeting, this study employed Cognitive Task Analysis (CTA) to capture the knowledge experts use to carry out differentiation. The results revealed a 4:9:2 skill formula across the preparation, implementation, and evaluation phases. Notable differences across school levels emerged. In the preparation phase, primary and secondary school teachers prepared varied materials (34%) and grouping strategies (44%), whereas only a few kindergarten teachers (3%) employed these strategies. In the implementation phase, most primary (68%) and secondary (79%) teachers tailored materials to students' learning styles by offering content in multiple formats; however, only a small proportion of kindergarten teachers (26%) differentiated content, focusing instead on process differentiation and additional learning support. Despite the differing contexts, the study also identified cross-level similarities. Future research should investigate the long-term impacts of DI on student achievement and engagement, as well as examine DI practices in diverse educational settings.